Media Framing Analysis of Detik.com and Kompas.com in Reporting on the Death of a Family in Kalideres - Emeraldien, Fikry Zahria; Salsabila, Dhea; Aini, Aisyah Nurul; Ubaldo, Emil (Da’wa and Communication Faculty of the Sunan Ampel State Islamic University, Surabaya, Indonesia., 2023)
The mass media has specific objectives in every statement, namely to convince readers to be interested and engage in the discourse provided. The purpose of this research is to describe Robert Entman's framing scheme in the online media Detik.com and Kompas.com in reporting on the investigation process to the announcement of the final results of the case of the family's death in Kalideres. This study focuses on two Detik.com news articles titled